THE EFFECT OF DIAMETER VARIATION ON THE COMBUSTION CHARACTERISTICS OF METHYL LAURATE AND METHYL OLEATE DROPLETS - Saktyawan, Helmi; Santoso, Rangga; Yuliati, Lilis; Purnami, Purnami (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2026)
The demand for fuel continues to increase while the availability of fossil fuel energy is decreasing day by day. This study aims to investigate the effect of diameter variation on the combustion characteristics of methyl laurate and methyl oleate droplets. Observations were made on the combustion characteristic of methyl laurate and methyl oleate droplets at the diameter variation stage. This research uses the experimental method (experimental research). The independent variables include diameters of 0.7 mm, 0.8 mm, 0.9 mm, 1.00 mm, 1.1 mm, and 1.2 mm. The fuels employed in this study were methyl laurate and methyl oleate. The observed dependent variables included ignition delay time, burning time, droplet temperature, droplet diameter evolution, and flame height. The findings obtained from the visualization of ignition delay time for methyl oleate with varying diameters revealed that it is more challenging to ignite than methyl laurate. Furthermore, the burning time of methyl oleate with different diameters was found to exceed that of methyl laurate. It was observed that the droplet temperature of methyl oleate increased to a greater extent than the droplet temperature of methyl laurate. Furthermore, the flame height of methyl oleate was found to be higher and exhibited greater variability, in contrast to the more stable behavior exhibited by methyl laurate. The fluctuation in the diameter of methyl oleate is in contrast to the stability exhibited by methyl laurate with regard to increasing droplet size.